2015
DOI: 10.1039/c5cc04170h
|View full text |Cite
|
Sign up to set email alerts
|

A poly(ADP-ribose) polymerase-1 activity assay based on the FRET between a cationic conjugated polymer and supercharged green fluorescent protein

Abstract: A label-free and convenient strategy for PARP-1 activity assay and inhibitors assessment has been developed based on the fluorescence resonance energy transfer (FRET) between a cationic conjugated polymer (CCP) and supercharged green fluorescent protein (scGFP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…2,5 The large, negatively charged PAR dramatically changes the charge properties of the acceptor proteins and initiates immediate cellular response to DNA damage. 6 Because PARP-1 activity level was related to tumor grade and the efficacy outcome of inhibitor therapy. 7−9 It is of great significance to develop some sensitive and accurate PARP-1 activity detection method for clinical diagnosis and drug screening in the treatment of various cancers.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…2,5 The large, negatively charged PAR dramatically changes the charge properties of the acceptor proteins and initiates immediate cellular response to DNA damage. 6 Because PARP-1 activity level was related to tumor grade and the efficacy outcome of inhibitor therapy. 7−9 It is of great significance to develop some sensitive and accurate PARP-1 activity detection method for clinical diagnosis and drug screening in the treatment of various cancers.…”
mentioning
confidence: 99%
“…Tang et al reported a convenient strategy for PARP-1 and its inhibitors assessment on the basis of the fluorescence resonance energy transfer between a cationic conjugated polymer and negatively supercharged green fluorescent protein. 6 Recently, our group also developed a simple and sensitive colorimetric biosensor based on the negatively charged PAR inducing the aggregation of cetyltrimethylammonium bromide (CTAB)-coated gold nanorods (GNRs). When PAR formed by PARP-1 was added, an obvious decrease of absorbance and vivid color change were observed.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Most detection methods for PARP-1 are based on its catalyzed production of PAR that has a large number of negative charges, which can adsorb positively charged probes by electrostatic attraction 1315. These methods do not have good selectivity because of the high background signals.…”
Section: Introductionmentioning
confidence: 99%